Pinealectomy aggravates and melatonin administration attenuates brain damage in focal ischemia - Kilic, E; Gursoy-Özdemir, Y; Bolay, H; Kelestimur, H; Dalkara, T (Sage Publications Inc, 1999)
Large infarcts develop in pinealectomized rats subjected to middle cerebral artery occlusion, which was attributed to loss of antioxidant action of melatonin. However, melatonin also has vascular actions, and pinealectomy may induce hypertension. The authors investigated (1) whether hemodynamic factors contribute to infarct development in pinealectomized rats, (2) whether melatonin administration can reverse the unfavorable effect of pinealectomy on infarct formation, and (3) whether melatonin can reduce the infarct volume in nonpinealectomized rats subjected to focal transient ischemia (2 hours middle cerebral artery occlusion, 22 hours reperfusion). Rats were pinealectomized 3 months before ischemia to eliminate any possible action of pinealectomy-induced hypertension on stroke. Blood pressure and regional CBF values during ischemia and reperfusion were not significantly different between pinealectomized and sham-operated rats, suggesting that pinealectomy-induced increase in infarct was not related to hemodynamic factors. The infarct volume resumed to the level of sham-operated rats on melatonin administration. Injection of melatonin (4 mg/kg) before both ischemia and reperfusion reduced infarct volume by 40% and significantly improved neurologic deficit scores in pinealectomized as well as sham-operated rats subjected to middle cerebral artery occlusion. These data suggest that physiologic melatonin release as well as exogenously given melatonin has a neuroprotective action in focal cerebral ischemia.
Keywords: melatonin; pinealectomy; cerebral ischemia; neuroprotection; cerebral blood flow; antioxidants